PELATIHAN ZIG-ZAG RUN LEBIH EFEKTIF MENINGKATKAN KELINCAHAN MENGGIRING BOLA DARI PADA PELATIHAN SHUTLLE RUN DALAM PERMAINAN FUTSAL - Wora, Dionisius; Adiatmika, I Putu; Fufu, Oktovianus; Adiputra, N.; Muliarta, Made; Griadhi, Putu Adiartha (Sport and Fitness Journal, 2017)
Background: Agility is a physical ability to change directions quickly without any balance disturbances. This capability is required in futsal. To achieve the agility, a continuous and ISSN: 2302-688X Sport and Fitness Journal Volume 5, No.2, Juli 2017: 1-9 2 systematic training is necessary. Objective: This study was conducted to compare the effect of zig-zag run training and shuttle run drill towards the dribble agility in the game of futsal. Method: Experimental research design with pretest-post test control group over the students in PJKR study program PGRI University Kupang was employed. The sample consisted of 28 persons and was divided into two groups comprising 14 persons in each group. Group 1 was given the zig-zag run training while group 2 was given the shutlle run drill and both kinds of training lasted for 8 weeks with a frequency of exercise three times per week (24 sessions). The measurement instrument used was the dribble agility using the method of measurement by Nurhasan 2008. The measurements were conducted before and after the treatment. Result: The average of the dribble agility in futsal was tested using Paired t-test and the effect of decrease of the agility to dribble with the Independent t- test. The average of dribble execution time in group 1 before training was 15.6 ± 0.7 seconds, and after training was 11.2 ± 0.6 seconds with a difference of 4.4 seconds with 28.4% (p <0.05) increase of the percentage, while in group 2 the average of dribble execution time before training was 15.7 ± 0.6 seconds, and after training was 12.9 ± 0.6 seconds with a difference of 2.8 seconds with the percentage of decrease was 17.9% (p <0.05). Both Zig zag run training and shuttle run training affected the increase of dribble agility, however the Zig zag run training had more significant effect. Conclusion: It can be concluded that the zig-zag run training is more effective in improving the dribble agility than the shuttle run training. Suggestion: Due to this, it is recommended that the zig-zag run training shall be adopted for the sports that need agility because the zig zag training has been proven effective to improve the agility, therefore the zig zag training may also be used to improve the performance of certain sports.